2015
DOI: 10.3892/or.2015.4163
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment and characterization of cancer stem cells from a human non-small cell lung cancer cell line

Abstract: Abstract. Tumor cells from the same origin comprise different cell populations. Among them, cancer stem cells (CSCs) have higher tumorigenicity. It is necessary to enrich CSCs to determine an effective way to suppress and eliminate them. In the present study, using the non-adhesive culture system, tumor spheres were successfully generated from human A549 non-small cell lung cancer (NSCLC) cell line within 2 weeks. Compared to A549 adherent cells, sphere cells had a higher self-renewal ability and increased res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…On top of that, one of the distinctive characteristics of stem and progenitor cells is their ability to resist anoikis and to survive in non-adherent conditions ( Pastrana et al, 2011 ). These characteristics have been applied in sphere formation assays, such as neurosphere ( Reynolds and Weiss, 1992 ) or mammosphere ( Shaw et al, 2012 ) formation assays and, to some extent, also in lung cancer sphere formation assays ( Zhao et al, 2015 ). We applied this approach to isolate LSPCs.…”
Section: Resultsmentioning
confidence: 99%
“…On top of that, one of the distinctive characteristics of stem and progenitor cells is their ability to resist anoikis and to survive in non-adherent conditions ( Pastrana et al, 2011 ). These characteristics have been applied in sphere formation assays, such as neurosphere ( Reynolds and Weiss, 1992 ) or mammosphere ( Shaw et al, 2012 ) formation assays and, to some extent, also in lung cancer sphere formation assays ( Zhao et al, 2015 ). We applied this approach to isolate LSPCs.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the theory of cancer stem cells (CSCs), that cancers are maintained by subpopulations of tumor cells with features of stem cells and progenitors, has served as a focus of in-depth investigations in cancer research [5]. A research reported the principal involvement of CSCs in tumor progression, recurrence, and drug resistance [6]. CSCs due to their high tumorigenicity can be observed in multiple human cancers, with great significance in NSCLC [7].…”
Section: Introductionmentioning
confidence: 99%
“…The cell invasion assay was performed using 24-transwell chambers (Corning, Newyork, USA). The procedures were carried out as previously reported [ 12 ]. For soft agar colony formation assay, a layer of media with 0.5 % agarose was first plated onto the bottom of a 6-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor growth is sustained by a small number of tumor-initiating cells known as cancer stem cells (CSCs). Sox2, a gene expressed at high level in stem cells, also plays a vital role in the regenesis of lung CSCs [ 10 12 ]. It has been reported that the growth and metastasis of certain cancer cells were suppressed when Sox2 was down regulated suggesting Sox2 may be a potential target for cancer treatment [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%